Kesiapan Petani Menghadapi Peremajaan (Replanting) Kelapa Sawit Di Desa Rimba Jaya, Kabupaten Kampar - Setiawan, Donny; Ismiasih, Ismiasih; Listiyani, Listiyani (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This study aims to determine the replanting model carried out by oil palm farmers and to determine the readiness of farmers in facing repalnting in Rimba Jaya Village, Tapung Hulu District, Kampar Regency. The research method uses descriptive qualitative. The sample was determined by purposive sampling with a total sample of 30 farmers with the consideration that the farmers selected were currently reppanting oil palm. The results showed that the replanting model used by oil palm farmers was total replanting (TUT) of 70% and interplanting of 30%. Readiness of farmers in facing repalnting because they receive assistance from the government, have savings, have side jobs and own land other than what is replanting